2016
DOI: 10.1038/srep28737
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Campylobacter jejuni colonization and enteritis using a novel infant rabbit model

Abstract: A lack of relevant disease models for Campylobacter jejuni has long been an obstacle to research into this common enteric pathogen. Here we used an infant rabbit to study C. jejuni infection, which enables us to define several previously unknown but key features of the organism. C. jejuni is capable of systemic invasion in the rabbit, and developed a diarrhea symptom that mimicked that observed in many human campylobacteriosis. The large intestine was the most consistently colonized site and produced intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…In the current study, infected untreated rabbits showed marked disruption of the villous epithelial surface in the small intestine, damage of the brush border was noted in areas adjacent to bacteria that appeared to be bound to the epithelial cells, all appear to contribute to villus disruption and the breakdown of epithelial barrier function, this may be attributed to effacement of microvilli, re-distribution of cytoskeletal and tight junction proteins, and extrusion of epithelial cells in the small intestine as recorded by Nemelka et al (2009). Our histopathological finding revealed that microbial activities occurring mainly at the intestinal level and more significant than extraintestinal invasion as no histologic changes were seen in livers, kidneys, lungs, or mesenteric lymph nodes, that agreed with Shang et al (2016) who reported that peritoneal histopathologic evaluation revealed no significant changes in infected animals at anytime during the study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the current study, infected untreated rabbits showed marked disruption of the villous epithelial surface in the small intestine, damage of the brush border was noted in areas adjacent to bacteria that appeared to be bound to the epithelial cells, all appear to contribute to villus disruption and the breakdown of epithelial barrier function, this may be attributed to effacement of microvilli, re-distribution of cytoskeletal and tight junction proteins, and extrusion of epithelial cells in the small intestine as recorded by Nemelka et al (2009). Our histopathological finding revealed that microbial activities occurring mainly at the intestinal level and more significant than extraintestinal invasion as no histologic changes were seen in livers, kidneys, lungs, or mesenteric lymph nodes, that agreed with Shang et al (2016) who reported that peritoneal histopathologic evaluation revealed no significant changes in infected animals at anytime during the study.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical signs and pathological lesions produced in the rabbits like those observed in humans and other large-animal models. C. jejuni multiplied in the distal small intestine and cecum of rabbits with large populations of C. jejuni, indicating its possible role in the pathogenesis of campylobacteriosis (Shang et al, 2016). Although diarrhea resolved spontaneously by day 4 post infection, the untreated rabbits may excrete bacteria asymptomatically for as long as 2 wk, these results supported by Black et al (1988); Wassenaar and Blaser (1999).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The clinical symptoms range from moderate watery diarrhea to severe inflammatory diarrhea which may lead to complications including Guillain Barre’ Syndrome [13] . In developing countries C. jejuni is responsible for 0.4 episode of diarrhea per child per year [14].…”
Section: Introductionmentioning
confidence: 99%